2019
DOI: 10.1038/s41598-019-49975-4
|View full text |Cite|
|
Sign up to set email alerts
|

A mutation in the methionine aminopeptidase gene provides phage resistance in Streptococcus thermophilus

Abstract: Streptococcus thermophilus is a lactic acid bacterium widely used by the dairy industry for the manufacture of yogurt and specialty cheeses. It is also a Gram-positive bacterial model to study phage-host interactions. CRISPR-Cas systems are one of the most prevalent phage resistance mechanisms in S. thermophilus. Little information is available about other host factors involved in phage replication in this food-grade streptococcal species. We used the model strain S. thermophilus SMQ-301 and its virulent phage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 56 publications
1
8
1
Order By: Relevance
“…Phage adsorption assays revealed that in parallel to spacer acquisition, surface receptor mutations likely also play a role in phage resistance in S. mutans. This finding is in sharp contrast to those for S. thermophilus, where surface receptor mutations are less frequent (36,37). The receptor for phage M102AD is currently not known, and no universal mutation responsible for adsorption resistance could be found.…”
Section: Discussioncontrasting
confidence: 72%
“…Phage adsorption assays revealed that in parallel to spacer acquisition, surface receptor mutations likely also play a role in phage resistance in S. mutans. This finding is in sharp contrast to those for S. thermophilus, where surface receptor mutations are less frequent (36,37). The receptor for phage M102AD is currently not known, and no universal mutation responsible for adsorption resistance could be found.…”
Section: Discussioncontrasting
confidence: 72%
“…The selection of these mutants suggests taking advantage of different phage resistance mechanisms. For example, some of them may have mutations at the phage receptor level (19) or other host factors (20). However, many of these BIMs are obtained via their CRISPR-Cas systems (21).…”
mentioning
confidence: 99%
“…In these experiments, it is clear that the coevolutionary dynamics observed for S. thermophilus and its phage can be attributed to CRISPR-Cas-mediated immunity to the phage. Resistant bacteria only evolve if the CRISPR-Cas system is inactivated by either antisense RNA expression (76) or an anti-CRISPR (acr) gene encoded by the phage (77), with resistance due to mutations in either the receptor or intracellular host genes required for completing the phage life cycle. This system, therefore, corresponds well with the theoretical scenario in Fig.…”
Section: Lytic Phagementioning
confidence: 99%